2021
DOI: 10.3390/brainsci11050608
|View full text |Cite
|
Sign up to set email alerts
|

Many Faces of the Hidden Souls: Medical and Neurological Complications and Comorbidities in Disorders of Consciousness

Abstract: Early and goal-directed management of complications and comorbidities is imperative to facilitate neurorecovery and to optimize outcomes of disorders of consciousness (DoC). This is the first large retrospective cohort study on the primary medical and neurological complications and comorbidities in persons with DoC. A total of 146 patients admitted to a specialized inpatient DoC rehabilitation program from 1 January 2014 to 31 October 2018 were included. The incidences of those conditions since their initial b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 13 publications
(23 reference statements)
0
8
0
1
Order By: Relevance
“…The most commonly reported complications were infections, and non-infectious neurological alterations. Infectious complications were identified in 26 studies, with UTIs, pneumonia and cellulitis reported as the most common ( 17 , 26 – 28 , 31 , 34 36 , 38 , 41 , 46 48 , 51 53 , 55 , 57 – 59 , 61 , 64 , 66 69 ). Six studies noted infection to have occurred in over half of the study population ( 26 , 51 , 53 , 55 , 59 , 68 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most commonly reported complications were infections, and non-infectious neurological alterations. Infectious complications were identified in 26 studies, with UTIs, pneumonia and cellulitis reported as the most common ( 17 , 26 – 28 , 31 , 34 36 , 38 , 41 , 46 48 , 51 53 , 55 , 57 – 59 , 61 , 64 , 66 69 ). Six studies noted infection to have occurred in over half of the study population ( 26 , 51 , 53 , 55 , 59 , 68 ).…”
Section: Resultsmentioning
confidence: 99%
“…Six studies noted infection to have occurred in over half of the study population ( 26 , 51 , 53 , 55 , 59 , 68 ). Neurological alterations were reported in 20 studies, with a variety of complications reported, including alterations in cognition, challenging behaviours, hydrocephalus, stroke progression, epilepsy, seizure and seizure-like activity ( 17 , 26 , 28 , 29 , 31 , 34 36 , 43 , 46 , 47 , 51 , 52 , 57 , 59 , 61 , 64 , 67 69 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The admission criteria and screening process have previously been described in detail ( 17 ). In brief, pre-admission screening was performed to determine the appropriateness of admission to the specialized DoC program (i.e., to triage potential misdiagnosis of DoC).…”
Section: Methodsmentioning
confidence: 99%
“…While the field has seen major advancements in the detection of consciousness and in standardization of assessments ( 2 , 15 ), we hope to contribute by providing guidance for effective clinical rehabilitation and advocating for increased rehabilitative access for these patients. Recently, we summarized and proposed clinical approaches in the assessment of reversible causes, confounders, and mimics of DoC ( 17 ), spasticity management ( 18 ), and the application of GABAergic medication trials ( 19 ). It is notable that meaningful improvements can be observed out of the scope of commonly used scales, such as achievement of decannulation and initiation of oral diet, thereby facilitating remaining voluntary motor control, etc.…”
Section: Introductionmentioning
confidence: 99%